A Randomized Study of Minimally Invasive Percutaneous Nephrolithotomy (MPCNL) with the aid of a patented suctioning sheath in the treatment of renal calculus complicated by pyonephrosis by one surgery. Issue 1 (December 2016) - Huang, Jianrong; Song, Leming; Xie, Donghua; Li, Monong; Deng, Xiaolin; Hu, Min; Peng, Zuofeng; Liu, Tairong; Du, Chuance; Yao, Lei; Liu, Shengfeng; Guo, Shulin; et al.
Abstract Background Calculus pyonephrosis is difficult to manage. The aim of this study is to explore the value of a patented suctioning sheath assisted minimally invasive percutaneous nephrolithotomy (MPCNL) in the treatment of calculus pyonephrosis. Methods One hundred and eighty two patients with calculus pyonephrosis were randomizely divided into observation group (n = 91) and control group (n = 91). The control group was treated with MPCNL traditionally using peel-away sheath while the observation group was treated with MPCNL using the patented suctioning sheath. Results All the patients in the observation group underwent one stage surgical treatment, 14 patients in the control group underwent first-stage surgery with the rest of the group underwent one stage surgery. The complication rate was 12.1% in the observation group, significantly lower than the rate in the control group which was 51.6%; One surgery stone clearance in the observation group was 96.7% while it was 73.6% in the control group; operative time in the observation group was (54.5 ± 14.5) min, compared to (70.2 ± 11.7) min in the control group; the bleeding amount in the observation group was (126.4 ± 47.2) ml, compared to (321.6 ± 82.5) ml in the control group; the hospitalization duration for the observation group was (6.4 ± 2.3) days, compared to (10.6 ± 3.7) days in the control group. Comparison of the above indicators, the observation group was better than the control group with significant difference (p < 0.001 each). Conclusions Minimally invasive percutaneous nephrolithotomy with the aid of the patented suctioning sheath in the treatment of calculus pyonephrosis in one surgery is economic, practical, and warrants clinical promotion. Trial registration This study was registered with Chinese Clinical Trial Registry on May 18, 2016 (retrospective registration) with a trial registration number ofChiCTR-IOR-16008490 .